2007
DOI: 10.1152/ajpheart.01413.2006
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effects of stretch on IGF-I secretion from rat ventricular fibroblasts

Abstract: Mechanical force can induce a number of fundamental short- and long-term responses in myocardium. These include alterations in ECM, activation of cell-signaling pathways, altered gene regulation, changes in cell proliferation and growth, and secretion of a number of peptides and growth factors. It is now known that a number of these autocrine/paracrine factors are secreted from both cardiomyocytes and ventricular cardiac fibroblasts (CFb) in response to stretch. One such substance is IGF-I. IGF-I is an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…27 The function of IGF-1R-positive hCSCs is regulated by both IGF-1 and IGF-2 which exert opposite effects on the fate of these cells. Importantly, cardiomyocytes and fibroblasts surrounding hCSCs have the ability to secrete the IGF-1 and IGF-2 ligand, 28,29 suggesting that a cross-talk occurs within the cardiac niches where myocytes and fibroblasts function as supporting cells. 21,30 These cells may dictate the developmental decision of hCSCs according to the needs of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…27 The function of IGF-1R-positive hCSCs is regulated by both IGF-1 and IGF-2 which exert opposite effects on the fate of these cells. Importantly, cardiomyocytes and fibroblasts surrounding hCSCs have the ability to secrete the IGF-1 and IGF-2 ligand, 28,29 suggesting that a cross-talk occurs within the cardiac niches where myocytes and fibroblasts function as supporting cells. 21,30 These cells may dictate the developmental decision of hCSCs according to the needs of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on human osteoblast-like cells, continuous cyclic mechanical strain also caused an increase in IGF1, suggesting that mechanical cell loading alters local expression of growth factors and, thereby, bone formation (Cillo et al, 2000). Similar finding have been reported in other cells such a ventricular fibroblasts, in which cyclic stretch significantly increased the IGF1 secretion in a frequency-and time-dependent manner compared with controls (Hu et al, 2007). In previous immunohistochemical studies, we have demonstrated the presence of IGF2 in the human PDL (Gotz et al, 2006a).…”
Section: Discussionsupporting
confidence: 68%
“…This change of tension within the epithelium or the geometry of cells can be rather “random” and spread a few cells away, without necessarily having a greater effect on their immediate neighbors. Interestingly, cyclic mechanic stretch has been shown to enhance the hypertrophic growth of mammalian cardiomyocytes or chick skeletal muscle cells [4042], and several previous reports revealed that the IIS pathway is also involved in mechanical stretch-induced hypertrophy [42, 43]. …”
Section: Possible Mechanisms For Cchmentioning
confidence: 99%